MoM Analysis and Design of a Compact Coaxial-to-Microstrip Directional Coupler - Benabdallah, Nadia; Benahmed, Nasreddine; Bendimerad, Fethi Tarik; Benyoucef, Boumedienne (Scientific Research Publishing, 2011)
In order to overcome the main drawbacks of coaxial, waveguide, and stripline couplers, the analysis and the design of a compact coaxial-to-microstrip directional coupler convenient for power and antenna control application, are presented using the method of moments (MoM) in two dimensions. This technique is adapted to study the complex configuration of the line’s system, which does not have a simple analytical solution. The modeling of this structure consists in analyzing the primary inductive and capacitive matrices ([L] and [C]). When these matrices are determined, it is possible to calculate the inductive and capacitive coupling coefficients (kL and kC) and estimate the resulting scattering parameters of the coupler using an adapted numerical model. The coupler can be integrated into a printed circuit board (PCB) and operates over 17 to 35 dB coupling coefficients and is always compensated. The compensation is achieved by the proper displacement of a tuning ground plane with respect to the edge of the PCB from 0.1 to 3.3 mm. As an application, we present the design of a compact coupler with 7.5 × 4.8 × 25.8 mm of size and having approximately 20 dB of coupling coefficient at 2 GHz and a minimum directivity of 23.3 dB in the frequency range [0.1 - 4] GHz. In order to check our numerical calculations by the MoM we made simulations in 3D by using CST MICROWAVE STUDIO software for the same geometrical and physical parameters of our designed coupler. The results obtained by the two numerical models (MoM and CST) show a good agreement of the frequency responses of the coaxial-to-microstrip directional coupler. The studied structure represents a great improvement for high power measurement systems, since it has broad-band, good directivity, and can be easily designed and fabricated.
Keywords: Coaxial-to-Microstrip Coupler; Inhomogeneous Asymmetrical Coupler; A 20 dB Compact Directional Coupler; Analysis and Design; MoM Method; CST MICROWAVE STUDIO Software